Dampak Pemberlakuan Kebijakan RED II Uni Eropa terhadap Ekspor CPO dan Implikasinya pada Perekonomian Nasional - Muhamad Yassar Naufal Subagja; Camelia Aprilianti; Nur Annisa Quraessin; Agnes Marianti Sormin (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This research analyzes the impact of the European Union's Renewable Energy Directive II (RED II) policy on Indonesia as the world's main palm oil producer. Using a qualitative method, data was obtained from scientific journals, previous studies, books, and media reports. The RED II policy that restricts the use of palm oil in biodiesel in the European Union has a significant impact on Indonesia's CPO industry, such as a decline in exports that affects foreign exchange, GDP contribution, and exchange rate stability. This article also discusses Indonesia's response, including diplomacy and sustainable palm oil promotion strategies, to maintain export stability and meet EU sustainability standards.